Lateral Stress Radiographs of Lateral Compression Type 1 Pelvic Injuries, With the Injured Side Down or Up, Reliably Measure Occult Instability. Issue 10 (October 2022) - Parry, Joshua A.; Hadeed, Michael M.; Strage, Katya E.; Heare, Austin; Stacey, Stephen C.; Mauffrey, Cyril
Abstract : Objectives: To evaluate the interobserver reliability of measured displacement and occult instability of minimally displaced lateral compression type 1 (LC1) fractures on lateral stress radiographs (LSRs) and to compare differences in displacement between LSR with the injured side down (ID) and up (IU). Design: Retrospective review. Setting: Urban Level 1 trauma center. Patients/Participants: Twenty-three adult patients with minimally displaced (<1 cm) LC1 injuries. Intervention: None. Main Outcome Measurements: Three orthopaedic surgeons measured the distance between the radiographic teardrops on LSR and supine anteroposterior pelvic radiographs to calculate dynamic fracture displacement. The interobserver reliability of the measured displacement, a continuous variable, was assessed by calculating the intraclass correlation coefficient. The interobserver reliability of occult instability (≥10 mm of displacement on LSR), a categorical variable, was assessed by calculating the kappa value. Matched-pairs analysis was performed to calculate the mean difference of measurements between observers and between ID and IU LSR. Results: The interobserver reliability of the measured displacement was excellent (intraclass correlation coefficient 0.93). The mean difference in measurements between observers ranged from −1.8 to 0.96 mm. The mean difference in the measured displacement between ID and IU LSRs for each observer ranged from −0.6 to 0.3 mm. There was 83% (19/23 cases) agreement on the presence of occult instability (≥10 mm of displacement on LSR) on both ID and IU LSRs. The interobserver reliability of occult instability was moderate (kappa 0.76). Conclusions: Measured fracture displacement and occult instability of minimally displaced LC1 injuries were reliably measured and identified on LSR, regardless of the laterality.